Shape variation and modularity of skull and teeth in domesticated horses and wild equids - Heck, Laura (Front Zool, 2018)
BACKGROUND: In horses, the morphological changes induced by the process of domestication are reportedly less pronounced than in other species, such as dogs or pigs – although the horses’ disparity has rarely been empirically tested. We investigated shape differences and modularity of domesticated horses, Przewalski’s horses, donkeys and zebras. Mandibular and tooth shape have been shown to be valuable features for differentiating wild and domesticated forms in some mammals. RESULTS: Both mandible and teeth, show a pattern of shape space occupation analogous to that of the cranium, with domesticated horses occupying a similar extension in shape space to that of wild equids. Only cranial shape data exhibit a tendency to separate domesticated horses and Przewalski’s horses from donkeys and zebras. Maximum likelihood model-based tests confirm the horse cranium is composed of six developmental modules, as reported for placental mammals in general. The magnitude of integration in domesticated horse skull was lower than in wild equids across all six cranial modules, and lower values of integration were associated with higher disparity values across all modules. CONCLUSION: This is the first study that combines different skeletal features for the description and comparison of shape changes in all living equid groups using geometric morphometrics. We support Darwin’s hypothesis that the shape variation in the skull of domesticated horses is similar to the shape variation of all wild equid species existing today. Lower magnitudes of module integration are recovered in domesticated horses compared to their wild relatives. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12983-018-0258-9) contains supplementary material, which is available to authorized users.